The boy from Birán. Reading of a child’s photo of Fidel Castro - Camacho Navarro, Enrique (2023)
This article analyzes a photograph of Fidel Castro that is very far from the epic stage of the guerrillero, but that is part of the iconography around this character. It is a portrait of Fidel at the age of three, taken in Birán in 1929, studied in order to understand the interests and intentions in its production, as well as the current uses of this image. Based on the consideration of photography as a social and cultural practice that integrates meanings, it must be incorporated in the study of history as a document that allows to provide information about their contexts of production and reproduction. From these considerations, it was possible to observe the meaning of the iconographic representation of Fidel at the age of three, who was photographed using conventions that highlighted the favorable economic conditions enjoyed by the Castro Ruz family, however, the study reveals that it has been added meanings in its subsequent uses, product of political interests around the Fidel’s guerrilla career.